2022
DOI: 10.1088/2053-1591/ac4aa1
|View full text |Cite
|
Sign up to set email alerts
|

A review on thin films, conducting polymers as sensor devices

Abstract: Thin film sensors are used to monitor environmental conditions by measuring the physical parameters. By using thin film technology, the sensors are capable of conducting precise measurements. Moreover, the measurements are stable and dependable. Furthermore, inexpensive sensor devices can be produced. In this paper, thin film technology for the design and fabrication of sensors that are used in various applications is reviewed. Further, the applications of thin film sensors in the fields of biomedical, energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 275 publications
0
32
0
2
Order By: Relevance
“…However, for composites without sonication (Figure 7(b) and (d)) more agglomerated particles can be observed that would allow the formation of conductive network. 17,26
Figure 7.Cross-sectional optical microscopy images of 4.5 vol% filler in Ag-PU composite, obtained by four different procedures: (a) casting with sonication, (b) casting without sonication, (c) spin-coated with sonication, and (d) spin-coated without sonication.
…”
Section: Resultsmentioning
confidence: 99%
“…However, for composites without sonication (Figure 7(b) and (d)) more agglomerated particles can be observed that would allow the formation of conductive network. 17,26
Figure 7.Cross-sectional optical microscopy images of 4.5 vol% filler in Ag-PU composite, obtained by four different procedures: (a) casting with sonication, (b) casting without sonication, (c) spin-coated with sonication, and (d) spin-coated without sonication.
…”
Section: Resultsmentioning
confidence: 99%
“…At present, traditional sensors based on inorganic or metal materials in the market usually have excellent electrical properties, durability, and compatibility. However, due to their stiffness, brittleness, hydrophobicity, and weak tensile properties, traditional sensors are not suitable for wearable sensors used for human motion detection [ 2 , 3 ]. Three-dimensional conductive hydrogels with excellent flexibility have received considerable attention as emerging materials with substantial applications as electronic skins, flexible wearable devices, multifunctional sensors, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of metallic nanoparticles, nanocrystals and films have been highly dynamic research areas due to their uses and developments for various applications, including imaging, sensing to catalysis. [1][2][3] Obtaining the desired metallic materials, free of contaminants, is essential for many applications. In that context, the use of organometallic or metallorganic precursors has shown to be advantageous.…”
Section: Introductionmentioning
confidence: 99%